(untitled) (Південний архів (історичні науки), 2025)
The relevance of the study is due to the defining role of social media in modern political processes and their special significance during the Revolution of Dignity in Ukraine. During this period, digital platforms acted as an effective space for mobilizing citizens, disseminating alternative information, and forming horizontal connections between protest participants. This helped to overcome the information monopoly of traditional media, ensure broad public support, and intensify international solidarity. Awareness of these processes is a necessary condition for analyzing the development of civil society and democratic transformations in Ukraine. The purpose of this article is to clarify the role of social media as a catalyst for socio-political change during the Revolution of Dignity, as well as to provide a comprehensive analysis of the long-term impact of this experience on the transformation of civic participation and the establishment of democratic institutions. The research methods include the analysis of scientific network sources, content analysis of social materials, as well as systemic and comparative approaches. Their use allowed to protect the regularity of the functioning of digital platforms during the period of mass protests, to identify key mechanisms of mobilization and features of digital communication.The results of the study showed that social media performed a complex function: they ensured the rapid dissemination of information, created conditions for self-organization of participants, facilitated international information exchange and formed a positive image of the protest movement. It has also been found that the multifunctionality of platforms has become the basis for the emergence of new forms of civic engagement, which has evolved from situational coordination to sustainable volunteer initiatives. The conclusions emphasize that social networks during the Revolution of Dignity were not only a communication tool, but also the main factor in the consolidation of civil society. They showed the ability to ensure the democratization of the activity of socio-political processes, contribute to the formation of new forms of citizenship and strengthen the value of freedom and solidarity.